1995
DOI: 10.1037/0278-7393.21.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Phonological similarity in the irrelevant speech effect: Within- or between-stream similarity?

Abstract: Irrelevant background speech disrupts serial recall of visually presented lists of verbal material. In 4 experiments, the hypothesis that this disruption is due to the phonological similarity of the irrelevant sound and the list to be recalled was tested. In Experiment 1, item length was controlled and a large irrelevant speech effect was found, but the effect of phonological similarity was small and confined to recency. In Experiment 2, words in the irrelevant stream were used, and the experiment showed an ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
158
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(178 citation statements)
references
References 24 publications
17
158
2
1
Order By: Relevance
“…The literature on irrelevant speech effects between single items and quiet conditions are somewhat mixed. Effects have been demonstrated with a repeated sound and even with a similar continuous sound compared to quiet in some experiments (Jones et al, 1992a(Jones et al, , 1992bLeCompte, 1995) while in others no reliable effect have been observed (Jones, 1994;Jones & Macken, 1995a,1995b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on irrelevant speech effects between single items and quiet conditions are somewhat mixed. Effects have been demonstrated with a repeated sound and even with a similar continuous sound compared to quiet in some experiments (Jones et al, 1992a(Jones et al, , 1992bLeCompte, 1995) while in others no reliable effect have been observed (Jones, 1994;Jones & Macken, 1995a,1995b.…”
Section: Resultsmentioning
confidence: 99%
“…It is clearly not due to simple masking effects as irrelevant items that are similar in sound to the remembered material cause no more disruption than dissimilar irrelevant sounds (Jones & Macken, 1995a, 1995bLarsen, Baddeley, & Andrade, 2000;LeCompte & Shaibe, 1997;Surprenant, Neath, & LeCompte, 1999). There is also a broad agreement with the view that disruption occurs principally when the irrelevant sound fluctuates, termed the 'changing-state hypothesis' by Jones (Jones, 1993;Jones et al, 1992aJones et al, , 1992bJones & Tremblay, 2000).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Originally, it was assumed that irrelevant sounds partially mask memory traces within the phonological store (Salamé & Baddeley, 1982, 1989. This view was later abandoned, as it is not in line with major characteristics of the ISE, such as its evocation by nonspeech sounds (Elliott, 2002;Jones & Macken, 1993), the impact of the sounds' changing state, and the finding that the ISE with speech is unaffected by the phonological similarity between the irrelevant speech and the memory items (Jones & Macken, 1995;Larsen, Baddeley, & Andrade, 2000). A more recent version of the phonological loop interpretation assumes that irrelevant sounds draw on domain-specific resources which build up a representation of the order in the to-be-remembered list (Page & Norris, 2003).…”
Section: The Phonological Loop Modelmentioning
confidence: 99%
“…The data provide solid evidence that a number of factors affect ISR performance, including the phonological similarity of list items (Conrad & Hull 1964;Baddeley 1968;Henson et al 1996;Farrell & Lewandowsky 2003;Page et al 2007 etc. ) and irrelevant sound during list presentation (Colle & Welsh 1976;Salamé & Baddeley 1982, 1986Jones & Macken 1995;Tremblay et al 2000 etc.). The detailed pattern of data underlying these and other effects has constituted a rich dataset on which to test competing models.…”
Section: Introductionmentioning
confidence: 99%